2007
DOI: 10.1007/s00436-007-0713-6
|View full text |Cite
|
Sign up to set email alerts
|

Crenosoma vulpis in dog: first case report in Italy and use of the FLOTAC technique for copromicroscopic diagnosis

Abstract: Crenosoma vulpis is a metastrongylid nematode that infects the bronchi, bronchioles, and trachea of wild and domestic canids and various other carnivores. It is endemic in the red fox population in the north-eastern parts of North America and in Europe, including Italy. Dogs are susceptible to infection with clinical signs consisting primarily in a chronic cough. The present paper reports-to the authors' knowledge-the first case of spontaneous C. vulpis infection in a dog in Italy. In addition, it also reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 12 publications
2
27
1
Order By: Relevance
“…Thus, the FLOTAC technique can be utilised for quantifying lungworm larva burdens in feline faecal samples because of its higher sensitivity compared to the other more widely used diagnostic tools; these results thus underscore previous observations made for various parasites of veterinary and human importance (Cringoli 2006;Rinaldi et al 2007b;Utzinger et al 2008), including the canine lungworm Crenososma vulpis (Rinaldi et al 2007a). …”
Section: Discussionsupporting
confidence: 66%
“…Thus, the FLOTAC technique can be utilised for quantifying lungworm larva burdens in feline faecal samples because of its higher sensitivity compared to the other more widely used diagnostic tools; these results thus underscore previous observations made for various parasites of veterinary and human importance (Cringoli 2006;Rinaldi et al 2007b;Utzinger et al 2008), including the canine lungworm Crenososma vulpis (Rinaldi et al 2007a). …”
Section: Discussionsupporting
confidence: 66%
“…The prevalence in dogs found in this study is slightly lower than the values found in Germany (0.9 % of 8438 dogs examined, Barutzki & Schaper, 2003; 2.4 % of 958 dogs Taubert et al, 2009) and in Denmark (1.4 % of 4151 dogs Taubert et al, 2009 ). In Italy C. vulpis was reported for the fi rst time in a dog in Campania by Rinaldi et al, (2007), and was recently found in kennels (18.4 % of the examined kennels) in the same region (Rinaldi et al, 2012). Respiratory capillariosis by E. aerophilus and E. boehmi are considered to be sporadic in pets, although the results of many studies in Italy and in other countries suggest that the presence of these two nematodes in domestic animals is most likely an underestimation (Burgess et al, 2008;Madeira de Carvalho et al, 2009;Di Cesare et al, 2011;Clark et al, 2013;Riggio et al, 2013;Veronesi et al, 2013).…”
Section: Discussioncontrasting
confidence: 76%
“…There is only one endemic focus in North America reported outside this northeastern region, occurring on St. Lawrence Island in Alaska (Rausch et al 1990). In Europe, C. vulpis is endemic in Austria, Belarus, Bulgaria, Croatia, Denmark, England, France, Germany, Hungary, Ireland, Italy, Netherlands, Norway, Spain and Switzerland (Barutzki and Schaper 2003;Beresford-Jones 1961;Borgsteede 1984;Coureil and Fornel 2006;Davidson et al 2006;Jancev and Genov 1988;Lassnig et al 1998;Manas et al 2005;Rajkovic-Janje et al 2002;Reilly et al 2000;Rinaldi et al 2007;Saeed et al 2006;Shimalov and Shimalov 2003;Sreter et al 2003;Unterer et al 2002;Willingham et al 1996). Recently, there has been a growing awareness that crenosomosis may play a greater role as a cause of chronic respiratory disease in dogs than previously recognised.…”
Section: Discussionmentioning
confidence: 97%
“…There are no age, breed or sex predispositions to infection. Diagnosis of crenosomosis in dogs is by detection of first-stage larvae in faecal samples by Baermann examination or FLOTAC device, techniques that tend to be infrequently utilised (Conboy 2004;Rinaldi et al 2007;Unterer et al 2002). Faecal flotation, much more widely used in veterinary practice as a diagnostic technique for parasitic infections, has poor detection sensitivity for the presence of L1 (current study ;Conboy 2004;Unterer et al 2002).…”
Section: Discussionmentioning
confidence: 98%